Immunomodulatory effects of dried Curcuma longa powder on the expression of crustin and lysozyme in Machrobachium rosenbergii dacqueti - Alambra, Jennifer R.; Alenton, Rod Russel R.; Gulpeo, Pia Clarisse R.; Mecenas, Christine L.; Miranda, Abigail P.; Thomas, Rey C.; Velando, Maden Krista S.; Vitug, Lawrence D.; Maningas, Mary Beth B. (2011)
Turmeric, a derivative of the plant Curcuma longa, exhibits pharmacological properties and its extracts were found to have a high potential to inhibit some pathogenic bacteria of shrimp and chicken. In this study, eighty (80) Macrobachium rosenbergii dacqueti juvenile shrimps were used for the entire experiment. Purchased turmeric was properly identified at the UST Herbarium. The turmeric was dried and pulverized; and its powder was incorporated into commercial feeds. The shrimps were divided into three group, D0, D1, and D7. D0 were fed with commercial feeds while D1 and D7 were fed with the enhanced shrimp feeds for one (1) and seven (7) days respectively. These were challenged with Vibrio alginolyticus. Relevant tissues were dissected from shrimp samples and total RNA was isolated, quantified with UV spectrophotometry and synthesized into cDNAs. RT-PCR was performed using crustin and lysozyme for target genes and EF-1α as standard control. Quality and quantity of RNA was assessed by measuring the A260/280 ratio and by agarose gel electrophoresis. An increasing intensity of crustin and lysozyme PCR bands relative to the duration of feeding was observed suggesting that shrimps fed with enhanced feeds after bacterial challenge had an induced expression of the mentioned antimicrobial peptides (AMPs). A remarkable increase in the expression of the two AMPs was also observed from D0 to D1 but not from D1 to D7. The results suggest that turmeric powder enhances the expression of these two peptides, but its rate of effectivity is yet to be studied.
Keywords: Shrimps; Biotechnology